2001
DOI: 10.1046/j.0021-8790.2001.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential post‐fledging survival of great and coal tits in relation to their condition and fledging date

Abstract: Summary 1.We present a multivariate model of the post-fledging survival of juvenile great and coal tits ( Parus major L. , P. ater L. ) in relation to chick body condition and timing of breeding. Radio-telemetry and colour marks were used to track tit families during 20 days from fledging, that is, the period of post-fledging dependence. Data on 342 chicks of 68 broods were obtained. 2. Forty-seven per cent of juveniles died during the observation period, predation being the main cause of mortality. In the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
474
8
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(508 citation statements)
references
References 46 publications
23
474
8
3
Order By: Relevance
“…Older, earlier-hatched nestlings may thus be the offspring of highquality breeders, showing enhanced survival and recruitment as a result of better genes, better parental care, or both. The positive effect of mass residuals on survival is consistent with an intuitive notion that the physical condition of nestlings is also a major determinant on individual fitness, possibly linked to parental quality and/or timing of breeding (20). With regard to the negative association between adrenocortical function and both survival and recruitment, there is evidence that the behavioral and physiological response to stress is consistent over time (8,10,12).…”
Section: Resultssupporting
confidence: 78%
“…Older, earlier-hatched nestlings may thus be the offspring of highquality breeders, showing enhanced survival and recruitment as a result of better genes, better parental care, or both. The positive effect of mass residuals on survival is consistent with an intuitive notion that the physical condition of nestlings is also a major determinant on individual fitness, possibly linked to parental quality and/or timing of breeding (20). With regard to the negative association between adrenocortical function and both survival and recruitment, there is evidence that the behavioral and physiological response to stress is consistent over time (8,10,12).…”
Section: Resultssupporting
confidence: 78%
“…For example, Naef-Daenzer et al (2001) found that Great Tit fledglings that died soon (,20 days) after fledging had 5% lower fledging mass than fledglings that survived. In our study, cuckoo nestlings that were fed plants, verte-brates, or both had lower fledging masses (by 20%, 20%, and 27%, respectively) than purely invertebrate-fed cuckoos.…”
Section: Potential Fitness Consequencesmentioning
confidence: 99%
“…Alternatively, there may be a threshold for parasitic burdens below which no compromise of growth is seen, and average nest burden on PC may have been below this threshold. Regardless of cause, nestlings from reclaimed wetlands may have to undergo compensatory gains before or just after fledging, and those that are unable to do so may suffer lower postfledging survival because of smaller body size, because postfledging survival is often correlated with body mass at fledging (Naef-Daenzer et al, 2001).…”
Section: Nestling Fitness and Blow Fly Infestationmentioning
confidence: 99%